Being Human and Being Alone: An Analysis of Herschel's Who Is Man? - AN, Ximeng (Journal of Research for Christianity in China (JRCC), 2025)
“Who is a person?” is essentially asking, “How does one become human?” “Who am I?” is fundamentally asking, “How does one become oneself?” To become human, to live as a person, the foremost task is to become oneself, to be oneself, to live authentically. The real challenge lies in the difficulty of living as a person. To be oneself, the foremost step is self-knowledge. Understanding the world and others begins with understanding oneself. “Who is man?” pertains to the act of being human, not merely a static state of being. “Who is man?” refers to who one will become, the future state. Man is perpetually planning and scheming. As a minority within the realm of existence, man occupies a point between God and beast. Man cannot live in isolation; he must connect with either one. Herschel believed that being human is the most unstable state. We are forced into freedom—free against our will—and dare to choose, scarcely knowing how or why. Herschel's anthropology emphasizes particularity and uniqueness over generality and regularity. The primary mode of being human is singularity.
Keywords: Loneliness, Being Human, Self-Reliance, Indecision, Uniqueness